Petrography, sulfide mineral chemistry, and sulfur isotope evidence for a hydrothermal imprint on Musina copper deposits, Limpopo Province, South Africa: Evidence for a breccia pipe origin?. (August 2016) - Chaumba, Jeff B.; Mundalamo, Humbulani R.; Ogola, Jason S.; Cox, J.A.; Fleisher, C.J.
Abstract: The Musina copper deposits are located in the Central Zone of the Limpopo orogenic belt in Limpopo Province, South Africa. We carried out a petrographic, sulfide composition, and δ 34 S study on samples from Artonvilla and Campbell copper deposits and a country rock granitic gneiss to Artonvilla Mine to place some constrains on the origin of these deposits. The assemblages at both Artonvilla and Campbell Mines of brecciated quartz, potassium feldspar, muscovite, chlorite, calcite, and amphibole are consistent with sericitic alteration. Quartz, amphibole, feldspars, and micas often display angular textures which are consistent with breccias. Sulfur concentrations in pyrite from Artonvilla Mine plot in a narrow range, from 50.2 wt. % to 55.7 wt. %. With the exception of a positive correlation between Fe and Cu, no well defined correlations are shown by data from the Musina copper deposits. The occurrence of sulfides both as inclusions in, or as interstitial phases in silicates, suggests that hydrothermal alteration that affected these deposits most likely helped concentrate the mineralization at the Musina copper deposits. Sulfur concentrations in chalcopyrite samples investigated vary widely whereas the copper concentrations in chalcopyrite are not unusually higher compared to those from chalcopyrite from other tectonic settings, probably indicating that either the Cu in the Musina copper deposits occurs in native form, and/or that it is hosted by other phases. This observation lends support to the Cu having been concentrated during a later hydrothermal event. One sample from Artonvilla Mine (AtCal01) yielded pyrite δ 34 S values of 3.1and 3.6‰ and chalcopyrite from the same sample yielded a value of 3.9‰. A country rock granitic gneiss to Artonvilla Mine yielded a δ 34 Spyrite value of 8.2‰. For Campbell Mine samples, one quartz vein sample has a δ 34 Spyrite value of 0.5‰ whereas chalcopyrite samples drilled from different areas within the same sample yielded values of 0.4 and 0.7‰. The same sample also yielded a δ 34 Sbornite value of 0.4‰. Another Campbell Mine quartz vein sample yielded a chalcopyrite δ 34 S value of −0.3‰. Sulfur isotope thermometry for one Campbell Mine quartz vein sample with coexisting sulfides yielded a Δ 34 Schalcopyrite-bornite value of 359 °C that is consistent with the stability of this mineral pair. Thus, δ 34 S values from Campbell Mine are consistent with an igneous source for the sulfur. Based on a simple two-end member isotope mixing model, contamination of the sulfur by sulfur derived from granitic country rocks likely occurred at Artonvilla Mine. Based on findings from this study and by other previous investigators, it is concluded that features displayed by the Musina copper deposits are consistent with a breccia pipe origin for the Musina copper deposits. Graphical abstract: